Microstructure characteristics and phase transformations of the Ni-P and Ni-P-Re electroless deposited coatings after heat treatment. (10th August 2016) - Wojewoda-Budka, J.; Wierzbicka-Miernik, A.; Litynska-Dobrzynska, L.; Szczerba, M.J.; Mordarski, G.; Mosiałek, M.; Huber, Z.; Zieba, P.
Abstract: The microstructure and phase composition of Ni-P and Ni-P-Re layers with medium phosphorus content of 8.8 and 8.2 wt. % of P, respectively, and 6.8 wt.% of Re electroless plated on copper substrate were studied. Both of the deposits showed amorphous X-ray profile, however, as it was expected, the presence of small (about 10 nm in size) nanocrystallites was observed in both kinds of plating under transmission electron microscope (TEM). The crystallization temperatures, measured in the range of 298–773 K, significantly increased with rhenium content as well as with increasing heating rate and differed by about 40 K. The activation energy calculated based on the Kissinger's model in the case of Ni-8.2P-6.8Re plating was 217.7 kJ mol −1 and for Ni-8.8 P was 206.3 kJ mol −1 . X-ray diffraction (XRD) measurements of the Ni-P deposits carried out after the heat treatment indicated the presence of the Ni and Ni3 P phases, which was confirmed by electron diffraction and high resolution observations in TEM. XRD data concerning Ni-P-Re plating revealed the following phases: Ni, Ni3 P, Ni0.21 Re0.79, Ni5 P2 and NiP, while TEM investigation confirmed the presence of Ni3 P, NiP, Ni5 P2 so far. Due to the very local information gathered from the TEM, this result needs further studies.